Developing integrative systematics in the informatics and genomic era, and calling for a global Biodiversity Cyberbank - Wen, Jun; Harris, AJ; Ickert‐Bond, Stefanie M.; Dikow, Rebecca; Wurdack, Kenneth; Zimmer, Elizabeth A. (Journal of systematics and evolution : JSE, 2017)
Systematics is the science of discovering, organizing and interpreting the diversity of all living organisms. Recent developments in genomics and biodiversity informatics are transforming systematics and have opened up many new opportunities. Major digitization efforts and developments in biodiversity informatics have helped the systematics community explore ways to enhance the efficiency in organizing, publishing, and utilizing systematic information. At the same time, genomics is rapidly facilitating construction of the tree of life, improving taxonomic classification, and disentangling complex evolutionary histories. In the informatics and genomics era, systematics has an incredible capacity to integrate with computational and exploratory platforms for discovery as well as with other, related disciplines while maintaining its core strengths in biological collections and morphology. We call for the establishment of a new global cyberinfrastructure or Biodiversity Cyberbank that will function as the main repository of many types of biodiversity data to ensure the long-term sustainability of the vast and growing amount of systematic data. This Biodiversity Cyberbank will contain new and efficient analytical pipelines for systematics research, especially for efficiently generating taxonomic treatments （revisions, e-monographs and floras）. integrative systematics requires the training of the next-generation systematists with taxonomic, phylogenomic and informatics skills to address grand questions about biodiversity and its assembly and continue to develop the Biodiversity Cyberbank. Integrative systematics must also proactively educate the public and policy makers on the importance of systematics and collections for addressing the biodiversity crisis of the Anthropocene, and a Biodiversity Cyberbank may represent one powerful tool for outreach.